2012
DOI: 10.1097/jsm.0b013e318266c735
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Preoperative MRI and MRA With Arthroscopically Proven Articular Cartilage Lesions of the Elbow

Abstract: This study demonstrates that MRI and MRA with a 1.5 T magnet, as used in community practice, have limited ability to detect cartilage lesions of the elbow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The authors suggested that contrast MRI was a preferable test in detecting biceps disease. Theodoropoulos et al 19 reported similar results with sensitivity of 67% and specificity of 100% for detecting overall disease of the biceps tendon. Likewise, Nourissat et al, 15 who examined only tendinopathy of the intra-articular portion of the long head of the biceps, reported low sensitivity of 43% and a higher specificity value of 75%.…”
Section: Discussionsupporting
confidence: 70%
“…The authors suggested that contrast MRI was a preferable test in detecting biceps disease. Theodoropoulos et al 19 reported similar results with sensitivity of 67% and specificity of 100% for detecting overall disease of the biceps tendon. Likewise, Nourissat et al, 15 who examined only tendinopathy of the intra-articular portion of the long head of the biceps, reported low sensitivity of 43% and a higher specificity value of 75%.…”
Section: Discussionsupporting
confidence: 70%
“…Arthrography is an older technique and its role is increasingly unclear in the era of advanced three-dimensional imaging techniques and protocols [12]. While the limits of resolution of elbow arthrograms on pediatric patients have not been evaluated, a recent study found that even magnetic resonance arthrography was inadequate in assessing articular cartilage lesions of the elbow [13]. The findings of this study further question the value of an intraoperative arthrogram in guiding surgical decision-making.…”
Section: Discussionmentioning
confidence: 94%
“…MRI is particularly valuable in determining OCD lesion stability and viability. 25 MRA (Figure 5) is particularly helpful in detecting loose bodies, but it does not improve the sensitivity for detecting cartilage lesions. 26 Imaging features associated with a worse prognosis are a displaced fragment, physeal closure of the capitellum or lateral epicondyle, and irregular contours of the articular surface or a high signal interface on T2-weighted MRI.…”
Section: Radiology and Classificationmentioning
confidence: 99%
“…MRI is particularly valuable in determining OCD lesion stability and viability. 25 MRA (Figure 5) is particularly helpful in detecting loose bodies, but it does not improve the sensitivity for detecting cartilage lesions. 26…”
Section: Radiology and Classificationmentioning
confidence: 99%